Bi2S3 nanorods encapsulated in iodine-doped graphene frameworks with enhanced potassium storage properties - Wei, Yi; Hou, Wenhui; Zhang, Peng; Soomro, Razium A.; Xu, Bin (Chinese chemical letters, 2022)
Bismuth sulfide (Bi2S3) is a promising anode material for high-performance potassium ion batteries due to its high theoretical capacity. However, the poor conductivity and substantial volume expansion hinder its practical application. We proposed an iodine-doped graphene encapsulated Bi2S3 nanorods composite (Bi2S3/IG) as an efficient anode for PIBs. The uniform-sized Bi2S3 nanorods evenly in-situ encapsulated in iodine-doped graphene framework, facilitating the electron transportation and structural stability. The potassium storage performance was evaluated in three electrolytes, with the best option of 5 mol/L KFSI in DME. The reversible capacity of representative Bi2S3/IG reached 453.5 mAh/g at 50 mA/g. Meanwhile, it could deliver an initial reversible capacity of 413.6 mAh/g at 100 mA/g, which maintained 256.9 mAh/g after 200 cycles. The proposed strategy contributes to improving potassium storage performance of metal sulfide anodes. Bi2S3 nanorods were in-situ encapsulated in iodine-doped graphene to construct a robust anode material for potassium ion batteries with competitive capacity, rate capability and cycling stability. [Display omitted]